Financial, Investment and Operational Cash Flow on Banking Performance in Indonesia - Simatupang, Apriani; Radityo Fajar Arianto (Universitas Pelita Harapan, 2024)
This study analyzes the influence of cash flows from funding activities or financial (CFF), investment (CFI), and operations (CFO) on Return on Assets (ROA) in the banking sector in Indonesia. Data was obtained from 40 banks listed on the Indonesia Stock Exchange (IDX) during 2010–2022 and analyzed using a fixed effects model panel regression. The results showed that only CFOs had a significant influence on ROA, but in a negative direction, indicating that an increase in operating cash flow was actually correlated with a decrease in ROA. CFF and CFI did not have a significant effect on ROA, indicating that funding and investment activities had less impact on profitability. The implications of this study emphasize the need for more strategic operational cash flow management to support asset efficiency and financial performance of banks.